2017
DOI: 10.1016/j.celrep.2017.10.040
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eif6 in Skeletal Muscle Homeostasis Revealed by Endurance Training Co-expression Networks

Abstract: SummaryRegular endurance training improves muscle oxidative capacity and reduces the risk of age-related disorders. Understanding the molecular networks underlying this phenomenon is crucial. Here, by exploiting the power of computational modeling, we show that endurance training induces profound changes in gene regulatory networks linking signaling and selective control of translation to energy metabolism and tissue remodeling. We discovered that knockdown of the mTOR-independent factor Eif6, which we predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
5
19
0
Order By: Relevance
“…Decades of research have demonstrated that skeletal muscle is one of the most dynamic tissues in the body. Muscle has an inherent ability to fine tune its response to environmental and physiological changes, including but not limited to exercise, diet, disuse, and disease [10][11][12][13]. Many adaptations of skeletal muscle are through transcriptional programs that modulate patterns of gene expression.…”
Section: Extensive Rna Processing In Muscle Biologymentioning
confidence: 99%
“…Decades of research have demonstrated that skeletal muscle is one of the most dynamic tissues in the body. Muscle has an inherent ability to fine tune its response to environmental and physiological changes, including but not limited to exercise, diet, disuse, and disease [10][11][12][13]. Many adaptations of skeletal muscle are through transcriptional programs that modulate patterns of gene expression.…”
Section: Extensive Rna Processing In Muscle Biologymentioning
confidence: 99%
“…EV pellets were digested and acidified as described previously (Clarke et al, 2017), and the completeness of digestion and bta-mir-181b target genes encoding BOLA class 1 (bovine MHC class 1), ICAM-1, and MMP-9 were amplified from TBL20 genomic DNA, using PfuUltra II Fusion HS DNA Polymerase (Agilent). EV pellets were digested and acidified as described previously (Clarke et al, 2017), and the completeness of digestion and bta-mir-181b target genes encoding BOLA class 1 (bovine MHC class 1), ICAM-1, and MMP-9 were amplified from TBL20 genomic DNA, using PfuUltra II Fusion HS DNA Polymerase (Agilent).…”
Section: Proteomic Sample Preparation and Lc-ms Analysismentioning
confidence: 99%
“…Six biological replicates were used for proteomic analysis of BL20-EV and TBL20-EV. EV pellets were digested and acidified as described previously (Clarke et al, 2017), and the completeness of digestion and bta-mir-181b target genes encoding BOLA class 1 (bovine MHC class 1), ICAM-1, and MMP-9 were amplified from TBL20 genomic DNA, using PfuUltra II Fusion HS DNA Polymerase (Agilent). These genes were selected based upon their potential importance in the pathogenesis of Theileria infection and relevance to disease progression.…”
Section: Proteomic Sample Preparation and Lc-ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar defects in translation are also observed in vivo, where livers of eIF6+/-mice are smaller, and exhibit an accumulation of inactive/empty (mRNA-free) 80S ribosomes compared to WT [17][18][19] . The lack of insulin-dependent stimulation of protein synthesis in the eIF6+/-mice has been associated with a reprogramming of fatty acid synthesis and glycolytic pathways with implications for muscle, liver and fat metabolism 19,21 .…”
Section: Introductionmentioning
confidence: 99%